Internierung und Militärdienst Die ,Lösung der Zigeunerfrage' in Österreich-Ungarn im Ersten Weltkrieg - Weigl, Marius (2022)
In 1918 according to the interior ministry in Vienna of the Republic of Austria there was no 'Gypsy mischief' anymore. The criminalization of poverty and the assumption about destitute persons would endanger the public order and security climaxed a new dimension in World War One, when more than one million refugees from the war zones arrived in the western regions of Austria-Hungary or were evacuated by the military forces. Following the internment camps for refugees and 'political suspicious' civilians, a 'Gypsies camp' was built in Hainburg an der Donau.